Can We Assess Early DNA Damage at the Molecular Scale by Radiation Track Structure Simulations? A Tetranucleosome Scenario in Geant4-DNA - Petrolli, Lorenzo; Tommasino, Francesco; Scifoni, Emanuele; Lattanzi, Gianluca (Frontiers in Physics, 2020)
Advanced track structure codes excel as state-of-the-art tools to low-scale dosimetric models: the rational evolution for a cell-like scenario is detailed within a microsecond of an ion collision, that is the standard timescale for critical DNA modifications. The in vitro DNA double-strand breaks (DSB) yield is matched indirectly by nanodosimetric track structure assessments; however, the score to specific DSB motifs (i.e., the yield associated to each DSB distance between DNA cuts) is mostly overlooked. In this work, we extend the PDB4DNA example of the Geant4-DNA toolkit, to briefly assess the hit and DSB scores over a nucleosome tetramer framework (Protein Data Bank entry: 1zbb). We describe a critical scenario that biases the statistical significance for an event-by-event track structure assessment at the nanometric scale, based on a Shannon's entropy estimate of the volumetric hit score; finally, we draw a tentative correlation between the mean DSB quality and a proton track, and conclude that short-distanced DSBs by direct effect are favored within a Bragg peak-relevant energy range.